Therapeutic factors in the first stage of men’s domestic violence groups - Lindsay, Jocelyn; Roy, Valérie; Turcotte, Daniel; Montminy, Lyse (Groupwork, 2012)
This article reports on the qualitative findings of a Québec study on therapeutic factors (TFs) in three ongoing men’s domestic violence groups. The study’s aim was to discover which TFs are important for male group members in their first stage of the group, and in particular, to explore how these men experienced and described universality. A content analysis was performed on interviews conducted with 72 group members following their third group session. We found that what was most important to the men was the knowledge they acquired about domestic violence, being able to share common concerns, and helping other members. The second part of the article reports on our qualitative analysis of universality, one of the most important TFs: how it was experienced by group members and how it became operational in the group. We believe that the methods of analysis developed in this study – examining symbols, characteristics, processes, and effects of TFs – can contribute to our understanding of the underlying elements of group work as an intervention method.